1992
DOI: 10.1152/jappl.1992.72.6.2475
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous injury in isolated sheep lungs: role of resident polymorphonuclear leukocytes

Abstract: Perfusion of isolated sheep lungs with homologous blood caused pulmonary hypertension and edema that was not altered by depletion of perfusate polymorphonuclear (PMN) leukocytes (D. B. Pearse et al., J. Appl. Physiol. 66: 1287-1296, 1989). The purpose of this study was to evaluate the role of resident PMN leukocytes in this injury. First, we quantified the content and activation of lung PMN leukocytes before and during perfusion of eight isolated sheep lungs with a constant flow (100 ml.kg-1.min-1) of homologo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…These findings are in line with ex vivo animal studies in which the authors show pulmonary edema after transfusion of aged blood without previous priming of the animals. [30][31][32] However, we stress that the effect of aged PLTs on lung injury was mild in this study and that pulmonary edema as a measure of pulmonary leak was absent. The results of this study need to be interpreted within the limits of the model we Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with ex vivo animal studies in which the authors show pulmonary edema after transfusion of aged blood without previous priming of the animals. [30][31][32] However, we stress that the effect of aged PLTs on lung injury was mild in this study and that pulmonary edema as a measure of pulmonary leak was absent. The results of this study need to be interpreted within the limits of the model we Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…With the hydrostatic edema, when the pressure was returned to control, the lymph flow fell toward control. Others have shown that, during both hydrostatic and permeability edema in the pulmonary vasculature, lymph flow parallels changes in filtration (13,17). That lymph flow remained elevated with the permeability edema suggested that either extravasation persisted or that lymphatic vessels associated with airways respond and maintain increased pumping for as long as edematous conditions persist.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of lymph flow has been correlated with the rate of filtration from the pulmonary vasculature but not with the amount of fluid that has accumulated (13). Even during conditions of permeability edema where extravascular fluid accumulation is elevated, lymph flow parallels fluid filtration and not overall lung water (17). Although the lymphatic vessels course through the perivascular cuffs, there appears to be little or no mixing between the lymphatic fluid and the interstitial fluid in the cuffs (7).…”
mentioning
confidence: 99%
“…28 Some groups have emphasized the use of blood over acellular colloid-buffered perfusates, 29,30 whereas others have observed spontaneous lung injury when using whole blood (edema and hypertension). 31 These effects were mitigated when using leukopenic and thrombocytopenic homologous blood with impaired platelet thromboxane release. 32 Clinically, the addition of leukocyte-reduced blood to a colloid-buffered solution has been proposed to improve tissue oxygenation during EVLP, 33 although no studies have been published demonstrating the superiority of either perfusate strategy (blood ϩ buffered solution, or buffered solution ϩ colloid).…”
Section: Perfusate Compositionmentioning
confidence: 99%